Buried affect: the lyric "moment" in Peter Riley's Excavations. Issue 2 (1st February 2020) - Bordell, Will
ABSTRACT: This article discusses Peter Riley's Excavations (1995–2004), a collection of 181 prose poems about Neolithic tumuli in the north of England, based on the accounts of J.R. Mortimer and William Greenwell. I argue that Riley combines different registers and voices to recuperate lyric as a moment rather than a genre. The first section discusses how syntactical, symbolic and vocal effects generate the 'grounded relativism' that Riley desires. I go on to resituate Riley's use of the prose poem alongside Charles Baudelaire and Jack Spicer instead of J.H. Prynne and the 'Cambridge school'. The third part analyses how the lyric voice of Excavations changes over the course of the collection, becoming less effective and affective as its ambitions are made all the more explicit. Ultimately, I conclude that Riley's work has wider implications for recent debates about lyric utterance, particularly in the way it internalises critical scepticism towards its own project.